PENGUATAN IDEOLOGI DALAM PEMBANGUNAN POLITIK: Kasus Koalisi Partai Pendukung di Provinsi Jambi - Karim, Navarin (Jurusan Ilmu Sosial dan Ilmu Politik Fakultas Hukum Universitas Jambi, 2018)
Diology since in the reform era almost nothing and seems to die in the political domain. The situation is different from the Old Order and the New Order. Determination of party choice is no longer based on ideology, but is more based on interests. Similarly, in party coalitions support candidates in Pemilukada. Whereas the derivative of Idiology is the principle. If someone is not strong in political ideology, it will be directly proportional to the weakness of a person's principle, someone's dust will be trapped in pragmatism. If the ideology is strong then will be depicted strong vision, mission, and program and jargon candidate in election kada. The public also no doubt choose the candidate, because there is a stigma as if the vision, mission, the program only as political accessories are made as a batman trap for voters. The purpose of this research is to strengthen ideology in political development and identify the stages of political development that need to be improved. Data collection method using primary and secondary data from KPUD, Political Parties in (Sarolangun, Muara Tebo and Jambi) Jambi Province. The analytical method uses qualitative analysis. The results of the study show that almost all candidates in post-conflict local elections are not supported by the coalition of parties with the same ideology and after analyzing the causes in addition to the main causes of too many parties whose ideology is the same and or almost the same.